Analysis of immittance component measurement methods of non-electrical nature objects - Антонюк, Олена Олександрівна; Походило, Євген Володимирович; Юзва, Володимир Зеновійович (Eastern-European Journal of Enterprise Technologies, 2015)
The relevance of measuring active and reactive immitance components for the quality assessment of non-electrical nature objects is substantiated in the paper. The authors have examined evaluation methods of the relative quality indicators of these objects. The analysis of immitance parameter measuring devices was performed in the paper, and it was found that there is a need for the implementation methods of serial devices for separate admittance parameter measurement in the frequency range. The methods that are implemented by serial measuring tools of the wide and special application were proposed. Analysis of these methods has shown that the active and reactive immitance components in comparison objects can be directly measured or determined by the measurement results of the module and the phase using appropriate available serial measuring tools. Measurement of these parameters of controlled and basic samples should be carried out by such tools using the replacement method. To build specialized immitance component measuring tools in a wide frequency range, combined methods, namely measuring one of the components (active or reactive) and module or phase angle with further calculation of another component are proposed. The component measurement results obtained by different methods can be considered identical within instrumental errors of measuring tools used, provided that the primary converter should be the same, the level of test sinusoidal signal must be the same, the connection of the primary converter is carried out by the same scheme, measurement conditions are the same. According to the proposed methods, specialized identification tools of non-electrical nature objects, using building block components can be developed.